Republic of Uruguay Integrated National Health System : Analysis of the Governability of the SNIS Benefit Plan - World Bank (Washington, DC, 2014)
Today the health reform in Uruguay is a mature, ongoing process in which major progress has been consolidated. At the same time, like all systems, it faces challenges in the immediate, medium, and long term, and how they are resolved will not only shape the ultimate outcome of many of the processes currently under way, and but will also impact the sustainability of the accomplishments so far. The purpose of this study is to contribute to development of the integrated national health system (SNIS) by analyzing and identifying policy options aimed at improving its governance, equity, efficiency, and sustainability through the government's use of control variables in order to achieve and maintain conditions of governability and efficiency, which will contribute to the stability and sustainability of the results. The present study analyzes the main variables that Uruguay has at its disposal to manage a central aspect of regulating the sector namely, the plan of benefits that the population receives to cover their health needs. This plan has important consequences for both health and the economy. The specific objectives of the study were to analyze the following three aspects of the SNIS: (i) the conditions of governance and governability of its benefit plan, (ii) methodological aspects of determining the premium to be received by insurers, and (iii) the capacity of the management information systems that are being used to monitor and evaluate the benefit plan. The document has three sections: (i) background; (ii) health coverage: critical aspects that affect its governability, specifically: (a) the benefit plan and the conditions of its governance, (b) the methodologies used to determine the premium, and (c) the health information systems used to monitor and evaluate the benefit plan; and (iii) conclusions and policy options. Finally, there are seven annexes that provide details on the topics discussed.